2023
DOI: 10.1159/000530424
|View full text |Cite
|
Sign up to set email alerts
|

Do Elderly Patients with Heart Failure and Reduced Ejection Fraction Benefit from Pharmacological Strategies for Prevention of Arrhythmic Events?

Abstract: Background Heart failure constitutes one of the leading causes of morbidity and mortality in Western countries, in which it is also the leading cause of hospitalization in elderly patients. The pharmacological therapy of patients with heart failure with reduced ejection fraction (HFrEF) has greatly improved during the last years. Summary The quadruple therapy (sacubitril/valsartan, beta-blockers, mineralocorticoid receptor antagonists, and sodium-glucose cotransporter 2 inhibitors) is nowadays the cornerstone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 86 publications
(98 reference statements)
2
1
0
Order By: Relevance
“…Following HF education intervention, the treatment outcomes for HF patients showed significant improvement, aligning with findings from previous studies 15,16 . This study found that the total effective rate of patients who received HF education intervention was higher than those who did not receive such intervention.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Following HF education intervention, the treatment outcomes for HF patients showed significant improvement, aligning with findings from previous studies 15,16 . This study found that the total effective rate of patients who received HF education intervention was higher than those who did not receive such intervention.…”
Section: Discussionsupporting
confidence: 88%
“…Following HF education intervention, the treatment outcomes for HF patients showed significant improvement, aligning with findings from previous studies. 15 , 16 This study found that the total effective rate of patients who received HF education intervention was higher than those who did not receive such intervention. Siennicka et al conducted a study on the long‐term effects of HF education intervention instable HF patients and observed significant improvements in their quality of life and functional motor abilities.…”
Section: Discussionmentioning
confidence: 75%
“…In certain studies, it has been observed that frail patients have less often guideline‐recommended medical treatment at discharge and follow‐up, 38 although they obtained the most significant benefit. 39 Our data show similar neurohormonal treatment prescriptions at discharge between frail and non‐frail patients but lower prescriptions in dependent patients than in independent ones.…”
Section: Discussionsupporting
confidence: 62%